Potensi Pembuatan Pupuk Dalam Bentuk Pelet Dari Bottom Ash Dan Fly Ash Industri Pulp Dan Kertas Untuk Hutan Tanaman Industri - Fortuna, Dewi; Helwani, Zuchra; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Bottom ash and fly ash derived from the ash burning bark in the boiler unit of the pulp and paper have the potential to be used as fertilizer because they contain macro and micro nutrients needed by plants. This study aims to determine the potential of bottom ash and fly ash as pellets. Physically, fertilizer in pellet form has smaller volume and easily stored and transported. The experiment were performed with two variable treatment which are the comparation of bottom ash with fly ash (0:100, 25:75,50:50, 75:25 and 100:0) and the adhesive doses (0%,0,5%,1% and 1,5%). The physical properties of resulting pellets were tested including density, water holding capacity, and durability. The effect of pellets on the growth of tomato plants were also carried out. Based on the analysis of research results the pellets meet minimum requirements of organic fertilizer and soil conditioner according to Indonesian National Standard (SNI 7847:2012) and PERMENTAN No.7 year 2011 unless C-Organic. The pelletization of fertilizer to the size of 5 mm can be done by adding adhesive cassava starch 1% with the physical properties of the pellets including a density of 1,724 g/mL, water holding capacity of 65,14% and durability of 93,89%. The use of pellet fertilizer with 100% fly ash has a good effect on the growth of tomato plants, seen from the growth of tomato stem height which is faster than without using pellet fertilizer. Keywords: bottom ash, cassava starch, fertilizer pellet, fly ash, tomato plants